Homocomposites of Polylactide (PLA) with Induced Interfacial Stereocomplex Crystallites - Arias, Veluska (ACS Sustain Chem Eng, 2015)
[Image: see text] The demand for “green” degradable composite materials increases with growing environmental awareness. The key challenge is achieving the preferred physical properties and maintaining their eco-attributes in terms of the degradability of the matrix and the filler. Herein, we have designed a series of “green” homocomposites materials based purely on polylactide (PLA) polymers with different structures. Film-extruded homocomposites were prepared by melt-blending PLA matrixes (which had different degrees of crystallinity) with PLLA and PLA stereocomplex (SC) particles. The PLLA and SC particles were spherical and with 300–500 nm size. Interfacial crystalline structures in the form of stereocomplexes were obtained for certain particulate-homocomposite formulations. These SC crystallites were found at the particle/matrix interface when adding PLLA particles to a PLA matrix with d-lactide units, as confirmed by XRD and DSC data analyses. For all homocomposites, the PLLA and SC particles acted as nucleating agents and enhanced the crystallization of the PLA matrixes. The SC particles were more rigid and had a higher Young’s modulus compared with the PLLA particles. The mechanical properties of the homocomposites varied with particle size, rigidity, and the interfacial adhesion between the particles and the matrix. An improved tensile strength in the homocomposites was achieved from the interfacial stereocomplex formation. Hereafter, homocomposites with tunable crystalline arrangements and subsequently physical properties, are promising alternatives in strive for eco-composites and by this, creating materials that are completely degradable and sustainable.